2011
DOI: 10.1182/blood-2011-06-364232
|View full text |Cite
|
Sign up to set email alerts
|

The risk of subsequent cancer and arterial cardiovascular events in patients with superficial vein thrombosis in the legs

Abstract: Although it has been clearly demonstrated that venous thromboembolism is associated with an increased risk of subsequent overt cancer and arterial cardiovascular events in comparison with control populations, whether this association also applies to patients with isolated (ie, without concomitant involvement of the deep vein system) superficial vein thrombosis (SVT) in the legs is unknown. In 737 consecutive patients with isolated SVT not involving the sapheno-femoral junction, we conducted a retrospective inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Whether the diagnosis of a symptomatic SVT is closely associated with occult cancer is discussed controversially. Findings from the Calisto trial suggest that patients with a SVT are not at an elevated risk to develop cancer in the following 26 months (Prandoni et al , 2011). In contrast, Sorensen et al (2012) were able to show that occurrence of SVT as well as DVT and PE is a pre-clinical marker of prevalent cancer, particularly during the first year after SVT diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the diagnosis of a symptomatic SVT is closely associated with occult cancer is discussed controversially. Findings from the Calisto trial suggest that patients with a SVT are not at an elevated risk to develop cancer in the following 26 months (Prandoni et al , 2011). In contrast, Sorensen et al (2012) were able to show that occurrence of SVT as well as DVT and PE is a pre-clinical marker of prevalent cancer, particularly during the first year after SVT diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of the risk of arterial events in 737 patients with an isolated SVT not involving the saphenofemoral junction, 13 Prandoni and colleagues found no increased risk compared with controls. In our study, we found a slightly higher risk of AMI and stroke subsequent to SVT (HR of 1.2 and 1.3, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…13 Although the studies described here offer some insight into the risk of DVT, PE, or arterial events after a SVT diagnosis, they have limitations, such as inclusion of patients with concurrent DVT or small or selected populations (trial or specialist referral settings). We therefore set out to study the association in a large, unselected population (ie, the entire population of Denmark).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a substudy of the Calisto trial, a trial in which ;3000 SVT patients with isolated SVT were randomized to either fondaparinux or placebo, Prandoni and coworkers compared 737 SVT patients with 1438 control patients with regard to cancer diagnoses during an average of 26 months of follow-up. 91 They concluded that occurrence of SVT in the legs does not represent a risk factor for subsequent malignancies. The same conclusion was drawn in a small study performed in the Netherlands.…”
Section: Superficial Venous Thrombosis and Cancermentioning
confidence: 99%